The profile of veterinary medicine in the light of socio-cultural variations: 11. occupational organizations - Abdullah Özen; Burhan Kemal Ateş (Eurasian Journal of Veterinary Sciences)
The aim of this study was to reveal the susceptibility of veterinarians on occupational organizations. A questionnaire survey was applied on 94 veterinarians working in various sectors in 22 provinces, most of which were located in the East and Southeast of the country. The results of the survey showed that veterinarians were organized in low proportions; the occupational organizations did not meet their expectations and they did not participate in the meeting of the Turkish Veterinary Medical Association. It was therefore concluded that veterinarians were not sensitive or. more importantly, conscious about occupational organizations.